Housing Stability and Neurocognitive Functioning in Homeless Adults With Mental Illness: A Subgroup Analysis of the At Home/Chez Soi Study - Stergiopoulos, Vicky; Naidu, Adonia; Schuler, Andrée; Bekele, Tsegaye; Nisenbaum, Rosane; Jbilou, Jalila; Latimer, Eric A.; Schütz, Christian; Twamley, Elizabeth W.; Rourke, Sean B. (Frontiers in Psychiatry, 2019)
Objective: This study examined the association of housing stability with neurocognitive outcomes of a well-characterized sample of homeless adults with mental illness over 18 months and sought to identify demographic and clinical variables associated with changes in neurocognitive functioning. Method: A total of 902 participants in the At Home/Chez Soi study completed neuropsychological measures 6 and 24 months after study enrollment to assess neurocognitive functioning, specifically verbal learning and memory, cognitive flexibility and complex processing speed. Multivariable linear regression was performed to assess the association of housing stability with changes in neurocognitive functioning between 6 and 24 months and to examine the effect of demographic and clinical variables on changes in neurocognitive functioning. Results: Overall neurocognitive impairment remained high over the study period (70% at 6 months and 67% at 24 months) with a small but significant improvement in the proportion of those experiencing more severe impairment (54% vs 49% p<0.002). Housing stability was not associated with any of the neuropsychological measures or domains examined; improvement in neurocognitive functioning was associated with younger age, and bipolar affective disorder at baseline. Conclusions: The high prevalence and persistence of overall neurocognitive impairment in our sample suggests targeted approaches to improve neurocognitive functioning merit consideration as part of health interventions to improve everyday functioning and outcomes for this population. Further efforts are needed to identify potential modifiable factors that contribute to improvement in cognitive functioning in homeless adults with mental illness.